Pelatihan Pembuatan Permen Jilat Sapi Sebagai Pakan Suplemen Pada Kelompok Pemuda Tani Ternak Maju Bersama Di Desa Penyaring Kecamatan Moyo Kabupaten Sumbawa - Noersidiq, Azhary; Dilaga, Syamsul Hidayat; Amin, Muhamad; Yanuarianto, Oscar; Suhubdy, Suhubdy; Dahlanuddin, Dahlanuddin; Fahrullah, Fahrullah; Maslami, Vebera (Universitas Mataram, 2023)
The partner involved in community service activities is the Maju Bersama Livestock Farmer Youth Group in Desa Penyaring Kecamatan Moyo Utara Kabupaten Sumbawa. The problems faced are that farmers are very dependent on the availability of forage feed but its availability is limited during the dry season and the lack of knowledge of farmers regarding the adequacy of feed nutrition to the needs of livestock and the lack of innovation of farmers to utilize or process local feed ingredients and agricultural waste that can be made as alternative feed and feed supplements. The purpose of this activity is to help farmers to increase cattle productivity by utilizing local feed ingredients from available agricultural waste and processed in the form of supplementary feed is